2019
DOI: 10.1108/bfj-06-2019-0469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of information on consumer preferences and willingness-to-pay for sparkling mock wines

Abstract: Purpose The purpose of this paper is to explore the role of information about alcohol content, organic labelling and packaging on consumer preferences and willingness-to-pay (WTP) of non-alcoholic sparkling mock wines. Design/methodology/approach In a two-step study, the consumer’s expectations and overall liking of two novel brands of mock wines were investigated by focus groups followed by a common hedonic test combined with a choice experiment aimed at measuring consumer WTP. A total of 240 consumers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…Two studies used functional magnetic resonance approaches to compare peoples’ reactions to lower-alcohol alternatives and higher-alcohol alternatives: one [ 65 ] found no differences between acute brain rewards in the consumption of beer with and without alcohol when presented in a context in which regular alcoholic beer is expected; the second study [ 66 ] found greater activation in brain regions that are sensitive to taste intensity in low-alcohol compared with high-alcohol wines, although the definition of low-alcohol wine in the study was 13–13.5% ABV. Two studies examined whether consumers were able to discriminate between alcoholic and non-alcoholic products; both found that consumers were able to distinguish between mock and real sparkling wine [ 67 ] and between alcohol-free spirits and alcoholic spirits [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies used functional magnetic resonance approaches to compare peoples’ reactions to lower-alcohol alternatives and higher-alcohol alternatives: one [ 65 ] found no differences between acute brain rewards in the consumption of beer with and without alcohol when presented in a context in which regular alcoholic beer is expected; the second study [ 66 ] found greater activation in brain regions that are sensitive to taste intensity in low-alcohol compared with high-alcohol wines, although the definition of low-alcohol wine in the study was 13–13.5% ABV. Two studies examined whether consumers were able to discriminate between alcoholic and non-alcoholic products; both found that consumers were able to distinguish between mock and real sparkling wine [ 67 ] and between alcohol-free spirits and alcoholic spirits [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies focused on the relationship between consumers' overall liking, specific individual aspects (i.e. individual traits, socio-economic aspects, specific attitudes) and WTP (see, for example, Naspetti et al ., 2020; Schouteten et al ., 2019; Teuber et al ., 2016, amongst others) instead. These studies did not confirm the connections between the individual components of liking and consumers' WTP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the overall global alcohol-free beer and dealcoholised wine market was valued at $20 billion in 2018 and is predicted to be valued at over $30 billion by 2025 (Naspetti, 2019). More specifically, the dealcoholised wine market is predicted to be worth more than $10 billion by 2027 (Shaw, 2020).…”
Section: Literature Perspectivesmentioning
confidence: 99%
“…When selecting a complex beverage, such as traditional wine or dealcoholised wine, consumers may find it difficult to choose, and therefore often rely on the product's attributes to assist them in making a final purchase decision (Nunes et al. , 2016; Naspetti, 2019). A comprehensive study that followed a scientometric approach to examine literature on wine selection and preference, found that consumers are not only influenced by the sensory profile and intrinsic attributes of the wine product, but also by the extrinsic attributes (Carollo et al ., 2022).…”
Section: Literature Perspectivesmentioning
confidence: 99%